Dari Pikiran ke Ucapan: Peran Memori Kerja, Kecemasan Matematika, dan Komunikasi Matematika dalam Pemecahan Masalah - Siskawati, Fury Styo; Suwito, Abi; Susanto (Cartesian: Jurnal Pendidikan Matematika, 2026)
This study aimed to describe the role of working memory, mathematics anxiety, and mathematical communication skills in mathematical problem solving. This study was based on the view that successful problem solving depended not only on mastery of concepts and procedures, but also on cognitive and affective factors, and students' ability to communicate their mathematical ideas. The used method was a systematic literature review of 20 Scopus-indexed international journal articles discussing the relationship between working memory, mathematics anxiety, mathematical communication, and problem solving. The results of the study indicate that working memory is positively related to mathematical problem solving and mathematical communication skills. Students with high working memory tend to be better able to understand problem texts, retain important information, choose strategies, and re-explain the solution process orally and in writing. Conversely, mathematics anxiety is negatively related to problem solving; high anxiety disrupts working memory function and reduces students' courage to participate in mathematical communication. Overall, mathematical problem solving is simultaneously influenced by working memory, mathematics anxiety, and mathematical communication skills. Therefore, mathematics learning needs to be designed by considering working memory load, anxiety management, and strengthening mathematical communication activities in the classroom.